Investigation of the 2017 Constitutional Amendment Referendum's Propaganda Materials of AK Party and CHP with Discourse Analysis - (:unkn) unknown (MARMARA UNIV, FAC COMMUNICATION, 2019)
Political actors, parties and leaders carry out motivational activities to support their own parties and organizations during each election period.. Political parties atry to influence the electorate by using as much communication tools as possible during the election period. Political actors need to use the arguments that would convince and thus influence the electorate. One of the most important studies on the significance of the argument in the process of political communication is the Argumentation Model of Steven Toulmin. In the theoretical background of this study, Toulmin's argumentation model has been studied. In the research part of the 2017 Constitutional Amendment Referendum, the persuasive documents of the leading representatives of the yes and no parties, AKP and CHP have been analyzed with the discourse analysis technique. Thus, it was tried to analyze which arguments the two parties put forward in their persuasive documents. Within the scope of the research study, the yes and no themed booklets and promotional videos prepared by AK Party and CHP were examined. As a result of the study, it was seen that both parties used the common arguments in both the written and video introductions in order to bring the voters to the point they wanted. As a result, it was observed that the use of arguments in political communication which was also was heavily used in the 2017 referendum - was an important tool in terms of persuasion.
Keywords: Stephen Toulmin; Argumentation; Referendum; Political Persuasion; Discourse Analysis